2012
DOI: 10.2172/1057022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Disruption Halo Current Toroidal Asymmetry in NSTX

Abstract: This paper describes the dynamics of disruption halo current non-axisymmetries in the lower divertor of the National Spherical Torus Experiment [M. Ono, et al. Nuclear Fusion 40, 557 (2000)]. While. The halo currents typically have a strongly asymmetric structure where they enter the divertor floor, and this asymmetry has been observed to complete up to 7 toroidal revolutions over the duration of the halo current pulse. However, the rotation speed and toroidal extend of the asymmetry can vary significantly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…• S. P. Gerhardt describes the dynamics of disruption halo current toroidal axisymmetries. They observed that the halo current have strongly asymmetric structure when enter the lower divertor [14].…”
Section: Introductionmentioning
confidence: 99%
“…• S. P. Gerhardt describes the dynamics of disruption halo current toroidal axisymmetries. They observed that the halo current have strongly asymmetric structure when enter the lower divertor [14].…”
Section: Introductionmentioning
confidence: 99%